Inquiry learning model effects on students' creative thinking in sensory system material - Sri Handayani Gea; Kartika Manalu (Inovasi Kurikulum, 2025)
Biology learning in various schools is still dominated by lecture and memorization methods that lack to develop students' creative thinking skills, especially in sensory system materials that require a deep understanding of concepts and practical applications. This study aims to analyze the influence of the inquiry learning model on the creative thinking ability of grade XI students of SMA Negeri 9 Medan on the sensory system material. The research method used is a quasi-experimental design with four classes as samples. Two experimental classes applied an inquiry learning model and two control classes used conventional learning. Data was collected through pretests and posttests that measured four indicators of creativity: fluency, flexibility, originality, and elaboration. The results showed a significant difference where the average posttest score of the experimental group was much higher than that of the control group, and showed a considerable difference. The results of the analysis showed that the data was normally distributed and had a homogeneous variance, so testing using the t-test could be carried out. These findings prove that the inquiry learning model is more effective in developing students' creative thinking skills because it provides opportunities to investigate, explore, and discover concepts independently, in contrast to conventional learning that relies solely on the transfer of information from teacher to student.   Abstrak Pembelajaran Biologi di berbagai sekolah masih didominasi oleh metode ceramah dan hafalan yang kurang mengembangkan kemampuan berpikir kreatif peserta didik, terlebih khususnya pada materi sistem indra yang memerlukan pemahaman konsep mendalam dan aplikasi praktis. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran inkuiri terhadap kemampuan berpikir kreatif peserta didik kelas XI SMA Negeri 9 Medan pada materi sistem indra. Metode penelitian yang digunakan adalah quasi-experimental design dengan empat kelas sebagai sampel. Dua kelas eksperimen menerapkan model pembelajaran inkuiri dan dua kelas kontrol menggunakan pembelajaran konvensional. Data dikumpulkan melalui pretest dan posttest yang mengukur empat indikator kreativitas: kelancaran (fluency), fleksibilitas (flexibility), orisinalitas (originality), dan elaborasi (elaboration). Hasil penelitian menunjukkan perbedaan signifikan dimana rata-rata skor posttest kelompok eksperimen jauh lebih tinggi dibandingkan kelompok kontrol, serta menunjukkan selisih yang cukup besar. Hasil analisis menunjukkan bahwa data berdistribusi normal dan memiliki varians yang homogeny, sehingga pengujian menggunakan uji t dapat dilaksanakan. Temuan ini membuktikan bahwa model pembelajaran inkuiri lebih efektif dalam mengembangkan kemampuan berpikir kreatif peserta didik karena memberikan kesempatan untuk menyelidiki, mengeksplorasi, dan menemukan konsep secara mandiri, berbeda dengan pembelajaran konvensional yang hanya mengandalkan transfer informasi dari guru ke peserta didik. Kata Kunci: berpikir kreatif; model pembelajaran inquiry; sistem indra